Physical Evaluation of Silage from Tithonia diversifolia and Panicum maximum: A Correlation-Based Approach: Evaluasi Kualitas Fisik Silase Campuran Tithonia diversifolia dan Panicum maximum: Pendekatan Analisis Korelasi - Ananta, Dwi Ananta; Fadilla Meidita; Nadia Rahma (Jurnal Tropicalanimal, 2025)
This study aimed to evaluate the physical and fermentative quality of silage produced from a mixture of Tithonia diversifolia leaves and Panicum maximum grass with 4% molasses addition. Five different mixing ratios (0:100, 25:75, 50:50, 75:25, and 100:0) were tested under a completely randomized design with three replications. The observed parameters included color, aroma, texture, and silage pH. Physical quality was assessed through sensory evaluation by trained panelists, while pH was measured using a digital pH meter. Results demonstrated that the ratio of forage mixtures significantly affected all physical parameters and silage pH (p < 0.05). The treatments with 50:50 and 75:25 ratios yielded the highest scores for color, aroma, and texture, as well as the lowest pH values, indicating optimal lactic acid fermentation. Correlation analysis revealed strong positive associations among physical parameters and a strong negative correlation between pH and sensory attributes. These findings suggest that silage formulations with 50-75% Tithonia diversifolia significantly enhance silage quality. The study highlights the potential of utilizing locally available forage and energy additives as a practical and economical strategy for improving year-round feed availability and quality in smallholder livestock systems.